Novel polynuclear copper compounds of halides and pseudo-halides - Reibenspies, Joseph Henry, author; Anderson, Oren, advisor; Elliott, C. Michael, committee member (Colorado State University. Libraries, 1987)
Mixed-valence compounds (one trinuclear (4) and two polymeric (5,6)) of copper(I,II) containing bridging cyano ligands and the ligands 1 (Pre-H) and 2 (cyclops) have been synthesized and characterized by single crystal X-ray diffraction. For 4, [Cu(1)(μ-NC)]2Cu(CN) · H2O, a= 9.723(2) Å, b = 10.908(2) A, c = 16.184(3) A, ɑ = 97.82(1) ᵒ, β = 103.64(2)ᵒ, γ= 92.21(2)ᵒ. Compound 5 ([Cu(1)(μ-NC)Cu(μ-CN)]n) occurs in three structural modifications. For 5a, a= 7 .755(2) Å, b = 13.179(3) Å, c = 16.508(5) A. For 5b, a= 7.878(2) Å, b = 8.418(2) Å, c = 25.874(4) Å, ~= 94.15(2)ᵒ. For 5c, a= 8.85(1) Å, b = 20.755(8) Å, c = 23.081(8) Å. For 6, [Cu(2)(μ-NC)Cu(μ- CN)·(l/2C6H6)]n, a= 11.667(2) Å, b = 8.962(2) Å, c = 19.895(5) Å,~= 97.58(2)ᵒ. The discrete molecules of 4 contain a trigonal planar [Cu(CN)3]^2- unit, which bridges between two [Cu(l)]+ complexes through two cyano ligands. Each of the polymeric species 5a, 5b, 5c, and 6 consists of a chain of [Cu(CN)2]- units joined by bridging cyano ligands. A cyano ligand also bridges between the copper(I) atoms of the chain and [Cu(1)]+ or [Cu(2)]+ complexes. The structures of three dinuclear copper(II) complexes, in which the Cu(II) atoms are bridged by azido and hydroxo ligands and by either the phenolate oxygen atom of N6OH or N6'OH have been determined by single crystal X-ray diffraction. The compound [Cu2(μ-l,3-N3)(N6O)](ClO4)2·THF (7) crystallized in the orthorhombic space group P 212121, with a= 12.977(2) Å, b = 13.188(3) Å, c = 22.033(6) Å. The compound [Cu2(μ-1,1-N3)(N6'O)](BF4)2·THF (8) crystallized in the orthorhombic space group P21cn, with a= 10.222(2) Å, b = 16.683(4) Å, c = 23.517(7) Å. The compound [Cu2(μ- OH)(N6'O)](BF4)i · THF (9a) crystallized in the monoclinic space group ?21/n, with a= 12.457(3) Å, b = 10.222(3) Å, c = 30.397(10) Å, β= 91.63(2). In these complexes each copper(II) atom is five-coordinate and is bound to three nitrogen atoms and the bridging phenoxo oxygen atom of either N60- or N6'0-. The fifth coordination site on each copper(II) atom is occupied by an atom of the bridging azido or hydroxo ligand. A dinuclear copper(II) complex which contains a bridging iodo ligand and two [Cu(2)]+ moieties has been characterized by X-ray crystallography. [Cu2(2)2I](ClO4) · 2MeOH (10) crystallized in the monoclinic system, space group C2/c, with Z = 4 and a= 21.564(3) Å, b = 11.920(2) Å, c = 14.831(2) Å, β = 96.83(1)ᵒ. Each of the copper(II) atoms in the dimer is coordinated to four nitrogen atoms of ligand 2 and to the bridging iodo ligand. The structures of two phases of the perchlorate salt of the copper(II) complex of 1 and methanol have been characterized by X-ray crystallography. For the room temperature phase {[Cu(1)]C1O4 · 1/2 MeOH}n (11a), a= 23.018(3) Å, b = 6.903(1) Å, c = 22.511(3) Å, β= 105.48(1)ᵒ. For the low temperature phase { [Cu(l)]ClO4 · 1/2 MeOH}i ((llb), a= 6.850(2) A, b = 11.886(3) A, c = 22.303(5) A, a= 75.26(2)0 , β= 88.97(2)ᵒ, γ= 73.38(2)ᵒ. When cooled, the crystalline solid 11 undergoes a reversible structural change. 11a is polymeric in nature, with bridging between copper atoms accomplished by an oxime oxygen atom of ligand 1. 11b is best described as dimeric.
Keywords: Copper compounds; Halides